Formation of healthy habits and lifestyles in university students: an intervention strategy/Formación de hábitos y estilos de vida saludables en estudiantes universitarios: una estrategia de intervención - Silvano Merced Len; Jorge Lázaro Coll Costa; Alionuska Velázquez Cintra (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
This article addresses the establishment of an intervention strategy to improve the physical fitness of Cuban university students, from the training process. It includes actions to maintain a healthy lifestyle based on the self-concept and conscious self -regulation of each individual. The objective was to propose an intervention strategy that contributes to the solution of the existing limitations, both in the methodological order and in the instrumental plane, and promotes the evaluation of the presence of systematic physical activity in the formation of habits and lifestyles health in Cuban university students. Among the theoretical methods used are the historical-logical, the analytical-synthetic and the induction-deduction. Empirical methods such as documentary review, statistics and survey were used. In data collection, measurement and descriptive statistics were used for information processing. The implementation of the strategy used students from the University of Informatics Sciences as a sample. As a result, the design of an intervention strategy that incorporates the systematic practice of physical activity and provides direct benefits in the quality of the university graduate is achieved.